Differentiating Lower Extremity Wounds: Arterial, Venous, Neurotrophic - Star, Ava (Seminars in Interventional Radiology, 2018)
Peripheral arterial disease (PAD) is a currently underdiagnosed and underrecognized vascular disease afflicting up to 200 million people worldwide, with at least 1 million of those suffering from critical limb ischemia (CLI). The 5-year mortality after major amputation for CLI (70%) is twice the average 5-year cancer mortality in the United States, and as many as 50% of CLI patients proceed directly to amputation without preceding vascular assessment or revascularization. Each year, twice as many breast augmentations are performed as leg revascularizations. Strong evidence in the literature supports markedly improved outcomes when multidisciplinary care teams across specialties are engaged to evaluate, treat, and manage patients with lower extremity wounds. This article assists the vascular specialist in differentiating the three most common lower extremity wound types.
Keywords: peripheral arterial disease; critical limb ischemia; lower extremity wounds; ulcers; interventional radiology